Dispersion and stability of solvent-free multi-walled carbon nanotube nanofluids. (18th May 2020) - Li, Yun; Yang, Long; Yu, Qiao; Yin, Xianze; Liu, Xiaohong; Huang, Hao; Liu, Weiqiang; Wang, Luoxin; Wang, Hua
Abstract: The fluidity of solvent-free nanofluids is related to the structure between and within molecules consisting of graftable groups or groups that can be exchanged. Research into controlling the fluidity by ion exchange have been reported. Indeed, it may be possible to control fluidity by surface grafting. This paper develops a facile method to prepare solvent-free multi-walled carbon nanotube nanofluids (MWCNTFs) with liquid-like behavior using surface grafted polyethylene glycol-substituted tertiary amines onto multi-walled carbon nanotubes (MWCNTs). The morphology, thermal stability, dispersibility and rheological behavior of MWCNTFs are investigated. It is found that MWCNTFs possess stable thermal properties and can flow without solvent existence. More importantly, the nanofluids show good dispersion and stability in water or other organic solvents for weeks due to the amphiphilic properties of the grafted groups. It is proposed that the facile method, which endows MWCNTs with better properties, will pave the way for developing high performance MWCNTs composites in the future.